Osteosarcoma-Derived Small Extracellular Vesicles Enhance Tumor Metastasis and Suppress Osteoclastogenesis by miR-146a-5p - Araki, Yoshihiro; Aiba, Hisaki; Yoshida, Takeshi; Yamamoto, Norio; Hayashi, Katsuhiro; Takeuchi, Akihiko; Miwa, Shinji; Igarashi, Kentaro; Nguyen, Tuan D.; Ishii, Kiyo-aki; Nojima, Takayuki; Takahashi, Satoru; et al. (Frontiers in Oncology, 2021)
N/A